Direct laser writing of vapour-responsive photonic arrays. Issue 35 (2nd September 2021) - Delaney, Colm; Qian, Jing; Zhang, Xia; Potyrailo, Radislav; Bradley, A. Louise; Florea, Larisa
Abstract : Combining structural design (led by FDTD simulations) and innovative hydrogel materials ( via ionic liquid cosolvents), we fabricate dynamic responsive photonic arrays. Abstract : Using direct laser writing, arrays of optically responsive ionogel structures were fabricated. To demonstrate their responsive nature, visible colour changes in the presence of different solvent vapours were investigated. This represents a new departure for photonic structural colouration, in which the fabricating structure shows a programmable, controllable, and dynamic stimuli response.